2013
DOI: 10.1111/jnu.12052
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Professional Identity Among Graduating Baccalaureate‐Prepared Nurses

Abstract: This study expands on what is known about patterns of professional identity among nurses and helps provide a beginning framework for understanding the values new graduates bring to practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, the suggestion "Interprofessional team training of nurses, physicians, and other health care providers should begin when they are students and proceed throughout their careers" [76]. Team culture was considered a strong influence in students' decision on whether to speak up or remain silent and is reflected in the relationship with their mentor and other team members [39,68] and was valued as a strong ethical responsibility to prevent errors [48]. Effective interprofessional collaboration has been found to prevent adverse patient safety events [68] as it challenges any gaps or misconceptions about the role of each discipline and responsibility in problem solving [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the suggestion "Interprofessional team training of nurses, physicians, and other health care providers should begin when they are students and proceed throughout their careers" [76]. Team culture was considered a strong influence in students' decision on whether to speak up or remain silent and is reflected in the relationship with their mentor and other team members [39,68] and was valued as a strong ethical responsibility to prevent errors [48]. Effective interprofessional collaboration has been found to prevent adverse patient safety events [68] as it challenges any gaps or misconceptions about the role of each discipline and responsibility in problem solving [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier evidence indicated that students felt more confident in technical aspects than the sociocultural aspects of patient safety [9,[44][45][46][47]. For example, students reported less knowledge regarding teamwork issues, especially during their clinical placements [35,46], although they valued teamwork ıncludıng patient participation in health care planning [48]. However, this evidence derived mainly from Canada, USA and Australia and partly from Europe (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is to our knowledge the first study of typologies of GPs in the referral process. Other studies on typologies in medicine have been done to explore professional identity of nurses [ 28 ] and hospital specialists [ 29 ]. Our two typologies represent aspects of the referral process where most GPs will recognize themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This is another outcome of clinical practice. Professional identity is consistent with values of nursing as a profession, such as caring, communication, leadership, and ethics, among others, and is a developmental process through the student's educational program (Hensel 2014;Hensel and Laux 2014). As students care for patients and interact with others in practice, they reflect on these values and what it means to be a nurse.…”
Section: Professional Identity Formationmentioning
confidence: 78%